Obstetric conditions and risk of first ever mental health contact during infancy, childhood and adolescence. - Liang, Wenbin; Chikritzhs, Tanya (Elsevier, 2011)
Objective: The main aim of this study was to investigate whether risk of first ever occasion of outpatient or inpatient service for a mental disorder among male children and adolescents may be associated with obstetric conditions. Design, setting and participants: this study was a population-based birth-cohort study of males born between 1980 and 1984 in Western Australia (WA). Males were identified using birth registry records and followed-up over a 19 year period using linked health data available through the Western Australian Data Linkage System. Measurements: Multivariate logistic regression was employed to estimate the risk of first ever mental health contact at different stages of mental development in childhood and adolescence. Main findings: Vacuum and forceps assisted delivery and emergency caesarean were associated with an increased risk of first ever mental health contact. The risk of first ever mental health contact was similar for spontaneous vaginal delivery and elective caesarean. Although outcomes varied by age group, children with stillborn siblings were at increased risk of first ever mental health contact as were babies with 7–9 Apgar score at 5 mins and those born to mothers with several previous live births. Conclusions and implications: Vacuum and forceps assisted delivery and/or the pathophysiological causes that lead to these clinical procedures, as well as other obstetric conditions, which maybe associated with (asymptomatic) brain injury at birth, which may increase the risk of mental disorders.